Cluster-Randomized Controlled Study of SMS Text Messages for Prevention of Mother-to-Child Transmission of HIV in Rural Kenya. (8th December 2016) - Kassaye, Seble G.; Ong'ech, John; Sirengo, Martin; Kose, Judith; Matu, Lucy; McOdida, Peter; Simiyu, Rogers; Syengo, Titus; Muthama, David; Machekano, Rhoderick
Abstract : Background . Antiretroviral medications are key for prevention of mother-to-child transmission (PMTCT) of HIV, and transmission mitigation is affected by service delivery, adherence, and retention. Methods . We conducted a cluster-randomized controlled study in 26 facilities in Nyanza, Kenya, to determine the efficacy of SMS text messages on PMTCT outcomes. The relative risk and confidence intervals were estimated at the facility level using STATA. Results . 550 women were enrolled, from June 2012 to July 2013. The median age was 25.6 years, and 85.3% received ARVs. Maternal ARV use was similar between the intervention and control arms: 254/261 (97.3%) versus 241/242 (99.6%) at 34–36 weeks of gestation and 234/247 (94.7%) versus 229/229 (100%) at delivery. Among infants, 199/246 (80.9%) and 209/232 (90.1%) received ARVs (RR: 0.91; 95% CI: 0.77–1.14); 88% versus 88.6% were tested for HIV at 6 weeks, with 1/243 (0.4%) and 3/217 (1.4%) positive results in the intervention and control arms, respectively. Communication increased in both the intervention and control arms, with the mean number of 7.5 (SD: 5.70) compared with 6 (SD: 9.96), p < 0.0001 . Conclusions . We identified high ARV uptake and infant HIV testing, with very low HIV transmission. Increased communication may influence health-seeking behaviors irrespective of technology. The long-term effectiveness of facilitated communication on PMTCT outcomes needs to be tested. The study has been registered on ClinicalTrials.gov under the identifierNCT01645865 .